Instagram as a participatory tool: A comparative analysis of six Spanish museums (Communication & Society, 2023)
Digital media is usually understood as a tool that helps the social and participatory ideal of museums and cultural institutions to materialize. This ideal has its roots in the reflections that, since the 1980s, new museology and critical museology movements have developed around the renewal of cultural organizations: a transformation that places the visitor at the center of the institution, revises their stories about its collections and invites institutions to be more participative with the public. Seeking to identify the characteristics that these theories adopt in practice, this article investigates the forms of participation implemented on Instagram by six Spanish cultural institutions: Museo Nacional del Prado Museum, Museo Nacional Thyssen-Bornemisza, Museo Nacional Reina Sofía, Museo Guggenheim Bilbao, Museo de Arte Contemporáneo de Barcelona (MACBA) and Centro de Cultura Contemporánea de Barcelona (CCCB). By way of a content analysis of their publications over the span of 6 months, patterns and trends have been identified within the communication strategies of these organizations. The results indicate a clear predominance of minimalist participatory forms (those oriented towards access to practical information and the discovery of collections) over maximalist modalities related to collaboration or co-creation. In general terms, there is also a considerable presence of audiovisual formats in the publications analyzed, showing the great capacity of these institutions to adapt to the latest changes in Instagram.